Green Synthesis of Silver Nanoparticles Using Aqueous Extract of Typha domingensis Pers. Pollen (qurraid) and Evaluate its Antibacterial Activity (Baghdad Science Journal, 2024)
In this study, the aqueous extract of (Typha domingensis Pers.) pollen grain (qurraid) to know its ability to manufacture silver nanoparticles. Qurraid is a semi-solid yellow food substance, sold in Basra markets and eaten by the local population. It is made from the pollen of the T.  domingensis Pers. plant after being pressed and treated with water vapor. The Gas chromatography–mass spectrometry (GC-MS) reaction was done to identify the active compounds of qurraid aqueous extract. The ability of the aqueous extract of qurraid to manufacture silver nanoparticles was tested, and the construction of silver nanoparticles was inferred by the reaction mixture's color, which ranged from yellow to dark brown. The synthesized silver nanoparticles (AgNPs) were described by UV-Vis, FTIR, XRD, SEM, and EDX. Then its anti-bacterial activity was estimated by the agar well diffusion method. The findings of the GC-MS analysis of the qurraid aqueous extract showed the major components with their ratio were: 5-Hydroxymethylfurfural with RT%  13.6196, 3-Deoxy-d-mannoic lactone 6.4285,. alpha.-L-lyxo-Hexopyranoside, methyl 3-amino-2,3,6-trideoxy- 4.264, 4H-Pyran-4-one, 2,3-dihydro-3,5-dihydroxy-6-methyl- 3.2078, and 1,3-Methylene-d-arabitol 3.1257. The construction of silver nanoparticles was described by spectroscopic methods, where the highest peak was recorded at 400nm by UV-Vis spectrum, which indicates the silver spectrum. The mineral nature of AgNPs was confirmed by XRD analysis, in which the highest peaks were, 111, 300, and 330 were recorded. In addition, the qrdAgNPs nanoparticles were spherical with sizes ranging from 20-70nm. The results of the EDX confirmed that the chemical composition of AgNPs was silver. The ability of the AgNPs was tested against four bacterial species, three of which were Gram-negative Escherichia coli A1, Escherichia coli A2, Alcaligenes faecalis AL1,  and the fourth was Gram-positive bacteria Bacillus zanthoxyli B1 , which were identified by traditional and molecular methods using 16SrRNA gene sequencing, antibacterial activity results of AgNPs  showed that it increases with increasing of  AgNPs concentration, and the most sensitive species to silver particles was  Alcaligenes faecalis AL1bacteria.